Correlating atom probe tomography with x-ray and electron spectroscopies to understand microstructure-activity relationships in electrocatalysts - Gault, Baptiste; Schweinar, Kevin; Zhang, Siyuan; Lahn, Leopold; Scheu, Christina; Kim, Se-Ho; Kasian, Olga (Mrs Bulletin, 2022)
The search for a new energy paradigm with net-zero carbon emissions requires new technologies for energy generation and storage that are at the crossroad between engineering, chemistry, physics, surface, and materials sciences. To keep pushing the inherent boundaries of device performance and lifetime, we need to step away from a cook-and-look approach and aim to establish the scientific ground to guide the design of new materials. This requires strong efforts in establishing bridges between microscopy and spectroscopy techniques, across multiple scales. Here, we discuss how the complementarities of x-ray- and electron-based spectroscopies and atom probe tomography can be exploited in the study of surfaces and subsurfaces to understand structure-property relationships in electrocatalysts.
CRIS-Team WoS Importer:2022-09-02